PENGARUH AL-QUR’AN DALAM PENDIDIKAN KARAKTER: (The Influence of the Quran in Character Education) - Zaenal Abidin Riam; Dini Khoirunnida (Raqib: Jurnal Studi Islam, 2025)
The Qur'an is the absolute and main guideline as a guide to life for its adherents. Although it is centuries old, the essence of the Qur'an remains intact and its benefits can still be felt today as a bearer of influence and guidance for human life. Among the teachings contained in it is the formation of character in a person. In living this short life, humans need to have character so that they are not easily swayed by the pleasures of the world that are fleeting. This is important so that a person can become a moral person, as emphasized in the Qur'an regarding the importance of character education that begins as early as possible and begins from the family. Based on this, this study focuses on deepening the Qur'an as a guideline for character education through a literature review methodology. The results of the study show that the Qur'an has a major influence on the process of forming a person's character. This character education includes two aspects, namely good morals and bad morals along with their various forms. In the long term, the values ​​of the Qur'an that contain character education are expected to strengthen and strengthen a person's personality in religion and society in the midst of an era full of tests and challenges.